Optimizing website development with rad for the center of digital transformation and tourism development - Singgalen, Yerik Afrianto (Jurnal Mantik, 2024)
This study explores the implementation of Rapid Application Development (RAD) frameworks in the design and optimization of websites for academic institutions, particularly focusing on enhancing the functionality of digital platforms used by study centers. By leveraging agile methodologies, this research aims to streamline the development process, ensuring that digital resources remain responsive to user needs and institutional objectives. The findings underscore the effectiveness of iterative prototyping and feedback integration in creating a user-centered design that significantly improves engagement and information accessibility. Furthermore, the study reveals how optimizing website content not only elevates the digital presence of study centers but also supports broader educational goals, such as fostering collaboration and expanding academic outreach. The analysis highlights the critical role of digital transformation in aligning technological advancements with strategic institutional missions. As a result, this research provides valuable insights into the practical application of RAD in optimizing digital infrastructures, ultimately contributing to the sustainable growth and innovation of academic environments